CONTRIBUCION AL CONOCIMIENTO DE DASYCOELIOXYS Mitchell (HYMENOPTERA, APOIDEA, MEGACHILIDAE) - Toro, H.; Fritz, M. (Acta Entomológica Chilena, 2022)
A key for the species of Dasycoelioxys Mitchell, as well as descriptions for the female of C. melcinopus and for the following new species: C. elizabeth, C. genisei, C. ¡juba, C. mapuche, C. pomona and C. ruzi are provided. New distributional records for C. melanopus Schulz and C. oriplanes Moure are given.